Interethnic Communication of Students During Their Studies at The University (Eurasian Journal of Learning and Academic Teaching, 2023)
Universities are often hailed as melting pots of diversity, where students from different ethnic backgrounds come together to pursue knowledge and personal growth. In this globalized world, international communication among students is not just an academic byproduct but an important component of their educational path. This article explores the importance of interethnic communication during university studies, the benefits it offers, the challenges it faces, and practical ways to foster greater understanding and harmony between diverse student populations